(untitled) (Conferencea, 2025)
This thesis reveals the theoretical aspects of self-development and improvement of current educators in order to use innovative ideas and technologies in organizing the modern educational process, and in this way, a comprehensive discussion is given on the methods and ways to improve students’ knowledge and bring education to a new level. It also highlights the theoretical basis for improving traditional teaching methods using modern methods in the educational process, and combining traditional teaching methods with new modernization methods.